Election news and agenda setting on Facebook by Malaysian English newspapers - Shafizan Mohamed,; Kamaruzzaman Abdul Manan,; Wan Norshira Wan Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article explores online news ability to on set the agendas of its readers on Facebook. Due to the decline in printed circulation, most contemporary newspaper organizations have opted to share their content on social media, most specifically, Facebook. By doing this, newspaper organizations are able to reach wider readership as well as facilitate more dynamic user engagements and interactions whereby readers are able to comment, discuss and even share a news piece. Within these dynamic user interactions, lies the potential for extending the agenda setting function of newspapers. On top of that also lies the newspapers’ ability to facilitate the readers’ opinions on issues. To confirm this relationship between online news, Facebook and public opinion, this article content analyzed reader comments on over 600 news articles from major English newspapers written during the Semenyih and Rantau byelections in Malaysia. Results of the analysis indicated that while the newspapers and its readers on Facebook do share some issue salience, the relationship does not adopt the traditional agenda-setting dynamic. The ability to communicate on Facebook has allowed the readers to do more than simply receiving news and issues. Instead, they disrupt the oftenstraightforward public opinion model by influencing how others receive news. Thus, newspapers’ contested relationship with the formation of public opinion is a significant change in the role of newspapers as the main agenda setter of political news.